Optical coherence tomographic angiography in central serouos chorioretinopathy - Chan, Szy Y.; Jonas, Jost B. (Retina, 2016)
Purpose: Using optical coherence tomographic angiography (OCT-angiography), we examined the vasculature of the choriocapillaris in patients with central serous chorioretinopathy (CSC). - Methods: The prospective observational clinical study included patients with CSC defined by painless loss of central visual acuity and presence of a serous macular detachment as visualized by spectral-domain OCT. All eyes underwent OCT-angiography. Subfoveal choroidal thickness and choriocapillaris width were measured. - Results: The study included 26 eyes of 21 patients with a mean age of 47.0 ± 7.9 years (range: 34-65 years). All 26 eyes showed an image pattern of high signal intensity, and 21 eyes additionally demonstrated dilated capillaries in the OCT-angio images. The areas showing abnormalities in the OCT-angiography were congruent with leaking areas in fluorescein angiography or areas with hyperpermeability in indocyanine green angiography. Among 16 patients with unilateral CSC, 1 patient showed a high intensity pattern in the OCT-angiogram in the contralateral, clinically unaffected eye. Parallel to thicker choroidal thickness measurements in affected eyes as compared with contralateral unaffected eyes in unilateral CSC, OCT-angiography revealed significantly thicker choriocapillaris measurements in the affected eyes. Conventional fluorescein angiography did not demonstrate leakage in 14 of 18 eyes with clinically diagnosed CSC. - Conclusion: Optical coherence tomographic angiography showed an image pattern of high signal intensity in all eyes with CSC and dilated vessels in the choriocapillaris in most eyes with clinically diagnosed CSC. The results indicate that OCT-angiography may become a noninvasive valuable tool for the diagnosis of CSC in particular and for the diagnosis of macular disorders in general.
Gesehen am 16.05.2019